.NET 2.0 Interoperability Recipes A Problem-Solution Approach - Bukovics, Bruce (Apress : Imprint: Apress, 2006)
.NET represents a new and improved way of developing software for the Windows platform. Given the chance, you'd probably rewrite all of your existing code in the newer managed code environment that .NET provides. But it is difficult or impossible to throw out all existing legacy code and start over when a new technology arrives. Instead, you need to find a way to move forward with new .NET development while reusing existing pieces of tested, working code. You need a way to interoperate with the existing code until you have a chance to finally rewrite all of it in .NET. The only recipe-style book on the subject, .NET 2.0 Interoperability Recipes: A Problem-Solution Approach guides Windows developers who are transitioning from native Windows code to .NET managed code. .NET tools will allow you to interoperate with existing code. But finding the appropriate tool for the task at hand can sometimes be a frustrating experience. So this book will guide you past myriad infrequently used interop options to focus on those youll use most often.